Overview of the Character Analysis of Libyan Olive Oil and their Advantages in Biomedical Applications - Allaq, Abdulmutalib Alabeed; Sidik, Norrizah Jaafar; Abdul-Aziz, Aziyah; Elengoe, Asita; Agha, Hasan Mohammed; Abdulrazzaq, Alaa Imad; Kouider, Fares (Journal of Asian Scientific Research, 2022)
Olive oil is depicted as "green gold" in Libya. It plays an inevitable role in Libyan food culture and countries’ economies. This review highlighted the most recent advances and challenges about the botanical classification of olives’, factors affecting olive oil quality and virgin olive oil processing techniques. Furthermore, this review explores the most significant attributes of olive oil in health and pharmaceutical applications. For instance, reduced pure olive oil considerably lowers the risk of cholesterol-related and other vascular diseases. Also exhibits excellent pharmaceutical properties for curing oxidative damage linked to cancer and neurodegenerative diseases. In addition, this review highlights the nutritional and food benefit of olive oil. Olive oil is an excellent antioxidant whereby olive oil can be applied to protect highly refined food such as meat from any pathogenic food spoilage. We hope that this review will give comprehensive knowledge about the health benefits of olive oil, which help to utilise oil in pharmaceuticals.